A comparative study on the clinical outcomes of local flap transfer and free flap transplantation for the repair of lower limb bone exposure wounds - Li, Xianglong; Zhao, Xiangbin; Guo, Kang; Li, Xueyang (Frontiers in Surgery, 2025)
ObjectiveTo compare and analyze the clinical outcomes of local flap transfer and free flap transplantation for the repair of lower limb bone exposure wounds.MethodsA retrospective study was conducted on 90 patients with lower limb bone exposure wounds admitted to our hospital from December 2022 to January 2024. Patients were divided into two groups based on the type of flap repair: the local flap group (n = 50) and the free flap group (n = 40). The local flap group underwent local flap transfer repair, while the free flap group underwent free flap transplantation repair. The two groups were compared in terms of surgical duration, intraoperative blood loss, hospital stay, complication incidence, and 1-year postoperative aesthetic satisfaction, functional recovery rate, and quality of life (SF-36 questionnaire).ResultsCompared with the local flap group, the free flap group had longer surgical duration, greater intraoperative blood loss, and shorter hospital stay, with statistically significant differences (P < 0.05). The incidence of complications in the local flap group (10.00%) was significantly lower than that in the free flap group (30.00%) (P < 0.05). One year postoperatively, the aesthetic satisfaction rate in the free flap group (92.50%) was slightly higher than that in the local flap group (82.00%), but the difference was not statistically significant (P = 0.145). The rate of excellent functional recovery in the free flap group (87.50%) was significantly higher than that in the local flap group (70.00%, P = 0.047), and the scores for eight dimensions of the SF-36 questionnaire, including physical pain and physical function, were significantly higher (all P < 0.01).ConclusionLocal flap transfer has the advantages of less surgical trauma and fewer complications; although free flap transplantation is more complex in operation and has a higher risk of complications, it has more advantages in functional recovery and improvement of quality of life.